Analisis Kesenian Jaran Kencak Menurut Perspektif Islam - azzahra, novia fatma (Maliki Interdisciplinary Journal, 2024)
In this study, the discussion will refer to the history of jaran kencak when viewed from an Islamic perspective with its development brought to Java, where Java is an area with a majority Islamic society. This study aims to find out the history of the development of jaran kencak art in Java and analyze the existence of jaran kencak art from an Islamic perspective as the times develop. This research is a historical research, so this research uses a qualitative method based on literature study with data collection from a natural setting, so that the process and intent based on the subject’s perspective are more displayed and the context is described comprehensively to facilitate academics in understanding the research. The results obtained are that Jaran Kencak art is an art that must be maintained and preserved, as a form of cultural and historical heritage that must be maintained. With its existence value that contains local cultural wisdom with Islamic value.